Comparison of the protective effects of selective endothelin-a receptor antagonist, ambrisentan, and dual endothelin-A/B receptor antagonist, bosentan, in experimental renal ischemia reperfusion injury - Kazımoğlu, Hatem; Uysal, Erdal; Batcıoğlu, Kadir; Petekkaya, Emine; Dokur, Mehmet; Karadağ, Mehmet; Gürer, Ahmet Orhan; Uyumlu, Burçin A. (Springer Science and Business Media LLC, 2020)
This study aims to compare the protective effects of ambrisentan, a selective endothelin typeA receptor antagonist, and bosentan, a dual endothelin typeA/B receptor antagonist, on experimental renal ischemia reperfusion injury.The study sample consisted of 21 female rats, which were divided into 3 groups: Control, Ambrisentan and Bosentan. For the ischemia-reperfusion injury model, left‑kidney nephrectomy was performed after sacrificing the animals. In the immunohistochemical examination, caspase-3 was examined, and then the apoptotic index was determined. In the biochemical examination, the activities of malondialdehyde (MDA), superoxide dismutase (SOD), glutathione peroxidase, and the levels of nitrite (NOx), TNF-α, and IL-1β were determined.There were statistically significant differences between the groups in terms of total injury score grade in range of 0‒3 (p=0.001).The glomerular and tubular apoptotic indices were higher in the control group as compared to those of the ambrisentan and bosentan groups (p=0.001).There were no statistically significant differences in terms of SOD, CAT, GPx, MDA, IL-1β and TNF-α measurements among the groups (p>0.05).In the experimentally created renal ischemia reperfusion model, both ambrisentan and bosentan increased the NOx level, decreased the apoptosis, and protected the kidney from renal ischemia reperfusion injury. However, no significant superiority was found between ambrisentan and bosentan in terms of their protective effects (Tab. 3, Fig. 2, Ref. 31).
Keywords: Endothelin Receptor Antagonists; kidney; ambrisentan; Apoptosis; Kidney; ischemia-reperfusion; Animals; rat; Ambrisentan; Ischemia-Reperfusion; Sulfonamides; bosentan; Phenylpropionates; Endothelins; apoptosis; Bosentan; Receptor, Endothelin A; Rats; Pyridazines; Reperfusion Injury; Rat; Female; 3. Good health